AN ANALYSIS OF RAINFALL EXTREMES IN THE NORTHERN SOUTH AMERICA AND THEIR BEHAVIORS FOR FUTURE CLIMATE BASED ON A1B SCENARIO - Fonseca, Paula; Veiga, José Augusto; Corrêa, Francis Wagner; Chan, Chou; Lyra, André (Revista Brasileira de Climatologia, 2021)
The Brazilian Amazon (BAMZ) and Northeast Brazil (NEB) regions have been facing intense climate extremes since the beginning of 21st century. In BAMZ, these climate extremes can modify the Amazon forest and its essential role in the local and remote climate. This study evaluated whether the extreme rainfall events in the both regions will be more intense and frequent in the future due to the increase of greenhouse gas emissions. An adapted version of the RX5day index was applied to distinguish between different types of extreme rainfall cases in the ETA model output for the decade 2089-2099 compared to the 1980-1990 decade. The results have shown that although the total rainfall is expected to be reduced by at least 1/3 (DJF) in the case of rare events, this kind of extreme rainfall will contribute with a higher amount of rainfall and will occur more frequently in both areas by the end of the 21st century. Heavy and very heavy events decrease for both areas (total rainfall amount and frequency). Results suggest that stakeholders must be prepared to cope with the population’s need for assistance during floods and rainfall reduction and reinforces the need to adapt to worse climate extremes projections.